Investigations of genes encoding proteins within the inflammatory pathway provides insight into the genetic susceptibility of achilles tendinopathy. Issue 4 (27th March 2011) - September, A V; Nell, E-M; Connell, K O; Cook, J; Handley, C J; Schwellnus, M P; Collins, M
Abstract : Background: Achilles tendinopathy (AT) is a multifactorial condition for which genetic risk factors have been identified. The evidence implicating cytokines and inflammatory mediators in the development of tendinopathy is growing. Objective: The objective of this study was to identify sequence variants within genes encoding proteins involved in the inflammatory pathway which may modulate risk of developing AT. Methods: A case-control genetic association study was conducted and candidate genes within the inflammatory pathway were explored. Functional polymorphisms within interleukin-1 (IL) (−31T>C and −511C>T), IL-1RN (VNTR) and IL-6 (−172G>C), were investigated for associations with AT in a South African (SA) and Australian (AUS) case-control study. A total of 356 (158 SA and 198 AUS) asymptomatic control participants (CON) and 171 (89 SA and 82 AUS) participants with AT (TEN) were genotyped. Genotype pairs were constructed using the above polymorphisms in combination with the COL5A1BstUI RFLP. Results: Risk-reducing genotypes were indentified and these genotypes in combination with the COL5A1BstUI CC genotype were found to significantly modulate risk of AT (p<0.025). No associations were observed for IL-1−31T>C, IL-1−511C>T or IL-1RN. The GG genotype (OR=2.1, 95% CI 1.2 to 3.6; p=0.017) and G allele (OR=1.5, 95% CI 1.0 to 2.2; p=0.044) of IL-6-172G>C were significantly over represented in AUS TEN. Conclusion: Variations within interleukin genes together with the COL5A1BstUI CC genotype are able to modulate risk of AT. This research emphasises that a pathway-based genetic association study may be a more effective approach to capture and understand the genetic risk factors underlying multifactorial conditions, such as AT. Furthermore, this study provides evidence that injury susceptibility is most likely dependent on the cumulative effect of the interactions of sequence variants in multiple genes within biologically significant pathways.